Atrial Arrhythmias after Pulmonary Resection: The Important Role of Pulmonary Vein Resection - Wei, Shenhai; Cui, Youbin; Xie, Mian; Wang, Guoqin; Kyutoku, Yasushi; Tian, Jintao; Song, Xiaoping; Chen, Yan (The Thoracic and Cardiovascular Surgeon, 2013)
Background Atrial arrhythmias (AAs) remain one of the most common complications after pulmonary resection. The association between postoperative AAs and pulmonary vein (PV) resection has not previously been clearly elucidated. A retrospective study on this issue is reported.Methods A total of 125 patients were involved in this study and all the performed surgical procedures and all postoperative AAs were carefully reviewed and recorded. A univariate and multivariate analyses were utilized to clarify the effect of PV resection on postoperative AAs.Results The overall incidence of postoperative AAs was 14.4% (n = 18). A stepwise increase in the incidence of AAs was observed from none, to the inferior of PV resection only, superior PV resection only and up to both inferior and superior PV resection (0, 3.1, 14.3, and 38.5%, respectively; p = 0.000). During multivariate analysis, PV resection was identified as an independent risk factor for postoperative AAs when it was entered either as an ordinal or as a categorical variable. The area under the receiver operating characteristic curve of PV resection revealed 0.786 (95% confidence interval [CI], 0.685–0.887), which was significantly larger than the extent of pulmonary resection (0.724; 95% CI, 0.637–0.800; p = 0.015).Conclusion PV resection plays an important role in the development of postoperative AAs after pulmonary resection and could be used as a good predictor for postoperative AAs.
Keywords: surgery complications; pulmonary arteries/veins; lung benign or congenital lesions; lung cancer treatment (surgery medical)